2015
DOI: 10.1021/acs.jpcc.5b00019
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid/Metal–Organic Framework Composites for H2S Removal from Natural Gas: A Computational Exploration

Abstract: The separation of H 2 S/CH 4 mixture was computationally examined in the composites of ionic liquids (ILs) supported on metal-organic frameworks (MOFs) at room temperature. Cu-TDPAT was selected as supporter for four types of ILs combined from identical cation [BMIM] + with different anions ([Cl] -, [Tf 2 N] -, [PF 6 ]and [BF 4 ] -). The results show that introducing ILs into Cu-TDPAT can greatly enhance the adsorption affinity towards H 2 S compared to the pristine MOF, and the strongest enhancement occurs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
100
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 67 publications
(117 reference statements)
1
100
0
Order By: Relevance
“…This body of literature can be summarized by two main goals: (1) the measurement of the phase behavior of CO 2 dissolved in ILs; and (2) the quantitation of CO 2 solubility in a bulk phase IL. As an example, in one recent study the solubility of CO 2 gas in [C 9 -imidazolium][PF 6 ] was shown to increase by~22% over a [C 4 -imidazolium][PF 6 ], as estimated from the liquid phase volume increase on going from low to high pressure at 298 K [43]. The main conclusion from all of this work is that CO 2 is effectively captured in the bulk IL phase.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…This body of literature can be summarized by two main goals: (1) the measurement of the phase behavior of CO 2 dissolved in ILs; and (2) the quantitation of CO 2 solubility in a bulk phase IL. As an example, in one recent study the solubility of CO 2 gas in [C 9 -imidazolium][PF 6 ] was shown to increase by~22% over a [C 4 -imidazolium][PF 6 ], as estimated from the liquid phase volume increase on going from low to high pressure at 298 K [43]. The main conclusion from all of this work is that CO 2 is effectively captured in the bulk IL phase.…”
Section: Introductionmentioning
confidence: 64%
“…RTILs are also designer solvents in the sense that a wide variety of cations and anions can be combined to tailor ILs for task-specific processes or reactions [1,2]. RTILs have unique characteristics, such as low volatility, non-flammability and water miscibility, that make them candidates for use in many applications, and has given rise to their use as cosolvents [3][4][5][6] in numerous applications [1,[3][4][5][6][7][8][9][10][11][12][13] that include electrochemistry [14][15][16], organic synthesis [17,18], gas separation/SLM's [19,20] and catalysis [17,21]. The inherent polar and nonpolar nanodomains that form in ILs allow them to readily solvate polar and non-polar solutes, and this has given rise to a significant increase in their study over the last decade [8,14,15,17,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The popularity of ILs has much to do with their interesting physicochemical properties, such as good solvents for a wide variety of organic and inorganic compounds, tunable solubility properties and negligible vapor pressure. Usually in MOFs synthesis, the ILs behave as solvents [154][155][156], reactants [157][158][159], structure directing agents [160][161][162][163][164], charge-compensating templates in anionic networks [165][166][167][168][169], functional inclusions [170][171][172][173][174][175][176], and as template. As mentioned in the previous section, a remarkable example of the MOF morphology controlled electrochemical synthesis in pure ionic liquid (IL) system was reported by Yang et al [143].…”
Section: Synthesis Of Mofs In the Presence Of Ionic Liquidsmentioning
confidence: 99%
“…Hydrogen sulfide is present in high concentrations within most natural gases, 2 but also in biogas 3 and landfill gas. 4,5 Currently, the most commonly used solutions for the removal of hydrogen sulfide are activated carbon and the Claus process.…”
Section: Introductionmentioning
confidence: 99%
“…However, its production is very expensive and the used up activated carbon can hardly be regenerated, thus most activated carbon has to be treated as hazardous waste after being used for H 2 S filtering purposes. 3,6 The Claus process operates above 900 • C, partly oxidizing the gas to produce water and atomic sulfur via the two steps given in equations (1) and (2). 1,7,8 H 2 S + 3/2 O 2 → H 2 S + SO 2 (1)…”
Section: Introductionmentioning
confidence: 99%